1992
DOI: 10.7326/0003-4819-116-6-461
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide in the Treatment of Acute Mountain Sickness: Clinical Efficacy and Effect on Gas Exchange

Abstract: In established cases of acute mountain sickness, treatment with acetazolamide relieves symptoms, improves arterial oxygenation, and prevents further impairment of pulmonary gas exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 13 publications
0
64
1
1
Order By: Relevance
“…Since the Pa,CO 2 values measured in the current study (table 3) are lower than values observed previously under similar circumstances [31,32] it is conceiveable that the subjects were hyperventilating to some degree, which might have increased their respiratory exchange ratio. Nevertheless, an association of a widened AaD,O 2 with AMS has been observed in several previous investigations [8,31,33]. In a study by BARTSCH et al [8], subjects with AMS revealed a transient decrease in isocapnic hypoxic ventilatory response (but neither in poikilocapnic hypoxic nor hypercapnic ventilatory response) within 4 h after arrival at 4,559 m, whereas this was not observed in controls.…”
Section: Discussionmentioning
confidence: 92%
“…Since the Pa,CO 2 values measured in the current study (table 3) are lower than values observed previously under similar circumstances [31,32] it is conceiveable that the subjects were hyperventilating to some degree, which might have increased their respiratory exchange ratio. Nevertheless, an association of a widened AaD,O 2 with AMS has been observed in several previous investigations [8,31,33]. In a study by BARTSCH et al [8], subjects with AMS revealed a transient decrease in isocapnic hypoxic ventilatory response (but neither in poikilocapnic hypoxic nor hypercapnic ventilatory response) within 4 h after arrival at 4,559 m, whereas this was not observed in controls.…”
Section: Discussionmentioning
confidence: 92%
“…Currently there are two other substances which may be effective in the prevention and treatment of AMS: acetazolamide and dexamethasone [6,26,28]. Therefore, the question arises as to whether there is a need for additional medication.…”
Section: Discussionmentioning
confidence: 99%
“…Rehydration does not treat AMS per se, but does address any dehydration, the symptoms of which can mimic those of AMS. Acetazolamide [129] and dexamethasone [121,130] can be added for those individuals with more severe AMS symptoms or those who fail to respond to conservative measures. Individuals who remain ill despite several days of these conservative measures should descend 500-1000 m or until symptoms resolve.…”
Section: Amsmentioning
confidence: 99%